2010
DOI: 10.1590/s0100-06832010000300037
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo e formas de cobre e zinco no solo após aplicações sucessivas de dejeto líquido de suínos

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 24 publications
2
48
0
25
Order By: Relevance
“…According to these authors, there was no increase in soil pH, and K and organic C after applying the organic fertilizer. Scherer et al (2010) found that in areas treated with swine waste in the long term (around 15 years, and between 20 and 25 years), the P, K, Cu and Zn concentrations increased markedly in the soil surface layers, especially in 0-0.05 m. Girotto et al (2010) found linear increases in available Cu and Zn concentrations in soil layers of a no-tillage area treated with 17 applications of up to 80 m 3 ha -1 of pig slurry over 78 months. According to the authors, the levels of available Cu and Zn in the 0-0.10 m soil layer of the treatment with the highest rate of organic fertilizer were, on average, 12 and 24 times higher, respectively, than in the control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these authors, there was no increase in soil pH, and K and organic C after applying the organic fertilizer. Scherer et al (2010) found that in areas treated with swine waste in the long term (around 15 years, and between 20 and 25 years), the P, K, Cu and Zn concentrations increased markedly in the soil surface layers, especially in 0-0.05 m. Girotto et al (2010) found linear increases in available Cu and Zn concentrations in soil layers of a no-tillage area treated with 17 applications of up to 80 m 3 ha -1 of pig slurry over 78 months. According to the authors, the levels of available Cu and Zn in the 0-0.10 m soil layer of the treatment with the highest rate of organic fertilizer were, on average, 12 and 24 times higher, respectively, than in the control.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports in the literature of increased levels of soil nutrients after pig slurry application under field conditions (Ceretta et al, 2003;Scherer et al, 2010;Girotto et al, 2010;Veiga et al, 2012). However, these studies used organic fertilizers with a higher dry matter content compared with the biofertilizer used in this experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the volume of manure produced on swine farms is usually great and crop fields are small, farmers frequently repeat applications of swine fertilizer on the same areas. Thus, nutrient contents in the soil are expected to increase over the years (Mcdowell et al, 2001;Basso et al, 2005;Gatiboni et al, 2008;Ceretta et al, 2010a,b;Girotto et al, 2010). The chemical properties related to soil acidity are also expected to change, e.g., with increases in soil pH and base saturation, as well as a decrease in aluminum saturation (Ceretta et al, 2003;Lourenzi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these elements may have been adsorbed due to the presence of iron oxides and OM, and to the pH reduction, factors that directly hamper its bioavailability and mobility in the system (Mellis et al, 2004). High Cu 2+ contents can cause phytotoxic effects (Sodré et al, 2014) and contaminate surface waters when transported through the sediments (Girotto et al, 2010). According to CQFSRS/SC (2004), the contents of Zn 2+ and Cu 2+ in the soil are considered as adequate for annual crops (> 0.5 mg dm 3 and > 0.4 mg dm 3 , respectively).…”
Section: Resultsmentioning
confidence: 99%